CONSECUENCIAS PSICOLÓGICAS Y EL USO EXCESIVO DE REDES SOCIALES EN LOS ADOLESCENTES DE BACHILLERATO DE LA UNIDAD EDUCATIVA 10 DE AGOSTO DEL CANTÓN MONTALVO. - ALARCON CHILUIZA PEDRO JULIO (2024)
Within the digital era, it has been observed that social networks have been transforming the form of communication, the way information is shared and the way of relating, mainly adolescents who are the most avid users of these platforms, which has generated a significant impact on psychological well-being. In this context, an investigation was carried out addressing the psychological consequences and excessive use of social networks; through which psychological well-being is explored from various perspectives, as well as the excessive use of these platforms. Adolescence is characterized by the search for identity and the need to belong, which is directly shaped by the omnipresence of social networks. Therefore, a correlational approach is adopted to explore and understand the statistical relationships between psychological consequences and excessive use of social media. Disorders such as anxiety, depression, stress and others can cause adolescents to isolate themselves and become attached to social networks, which can cause them to develop addiction to these digital platforms, in addition to causing alterations in their behavior. Therefore, various aspects are examined, such as loss of time control, disinterest in activities that were previously enjoyed, irritability and poor performance in daily activities. By exploring the link between these variables, essential information is provided for the formulation of educational and awareness strategies that encourage a healthy balance in social media use.